Selection of responsible management alternative for marine protected area using multi criteria decision analysis - Nair, Madhavan Balan; Ramachandran, Sridar; Shuib, Ahmad; Mohammad Afandi, Syamsul Herman (Faculty of Forestry, Universiti Putra Malaysia, 2013)
The aim of this paper is to present the methodological approach in selecting the optimal responsible management approach in managing the Tun Sakaran Marine Park (TSMP), which is located off the east coast of Sabah. The selection of responsible management uses a multi-criteria decision making approach. The initial phase requires the elicitation of decision-making criteria from the relevant stakeholders involved in the decision making process. They include park managers, senior government officials and village heads. The modified Delphi technique will be used to identify the decision-making criteria grouped into three initial themes; the social, economic and environment. In the following phase, the Analytical Hierarchy Process (AHP) will be used to arrange the criteria in a hierarchical form. This is to enable the pairwise comparison of the criteria towards choosing an alternative that satisfies the goal of responsible management.